Examination of electronic structure differences between CIGSSe and CZTSSe by photoluminescence study - Tai, Kong Fai (2015)
In this paper, we elaborate on the interpretation and use of photoluminescence (PL) measurements as they relate to the “donor/acceptor” and “electrostatic potential fluctuations” models for compensated semiconductors. Low-temperature (7 K) PL measurements were performed on high-efficiency Cu(In,Ga)(S,Se)2 and two Cu2ZnSn(S,Se)4 solar cells with high- and low-S/(S + Se) ratio, all fabricated by a hydrazine solution-processing method. From excitation-dependent PL, the total defect density (which include radiative and non-radiative defects) within the band gap (Eg) was estimated for each material and the consequent depth of the electrostatic potential fluctuation (γ) was calculated. The quasi-donor-acceptor pair (QDAP) density was estimated from the blue-shift magnitude of the QDAP PL peak position in power-dependent PL spectra. As a further verification, we show that the slope of the lifetime as a function of photon energies (dτ/dE) is consistent with our estimate for the magnitude of γ. Lastly, the energetic depth of the QDAP defects is examined by studying the spectral evolution of the PL as a function of temperature. The shallow defect levels in CIGSSe resulted in a significant blue-shift of the PL peak with temperature, whereas no obvious shift was observed for either CZTSSe sample, indicating an increase in the depth of the defects. Further improvement on Cu2ZnSn(S,Se)4 solar cell should focus on reducing the sub-Eg defect density and avoiding the formation of deep defects.